PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP REMAJA TENTANG SEKS BEBAS DI SMP NEGERI 8 AMBON - Petriana Mahmud; Yona Latuperisa (Pasapua Health Journal, 2020)
Introduction : Sex education is a way of teaching that can help adolescents to deal with life problems that stem from sexual urges. Free sex is a cultural influence that comes from the west and is then adopted by Indonesian people without filtering it first. The purpose of this study was to determine the effect of health education on the knowledge and attitudes of adolescents about free sex at SMP Negeri 8 Ambon. Method : This research uses a type of quantitative research, is descriptive. The population in this study were students of class VIII, totaling 87 people. Sampling in this study using accidental sampling technique with a total of 41 respondents. Results : In this study, using the chi-square test, it was found that 38 respondents (92.7%) had good health education, 3 (7.3%) had poor health education. Meanwhile, 22 (53.7%) had good knowledge of sex, 19 (46.3%) had poor knowledge of sex. And there were 33 (80.5%) who had a good attitude towards teenagers, 8 (19.5%) had a bad attitude about teenagers. With a significant value p = 0.144> 0.05 and p = 0.488> 0.05. Conclusion: Based on the results of statistical tests using the chi-square test, it showed that there was no effect of health education on the knowledge and attitudes of adolescents about free sex at SMP Negeri 8 Ambon.